Ganoderma lucidum, a Potential Revolutionary Macro Fungus in the Field of Medicine - Rani, Isha; Gupta, Mehak; Sharma, Samarth; Kaur, Gagandeep; Sharma, Pankaj (Current Traditional Medicine, 2025)
Ganoderma lucidum is a traditional Asian medication used in China, Korea, and Japan. It is a well-known medicinal fungus that is regarded as the elixir of life. Polysaccharides, proteins, enzymes, sterols, fatty acids, vitamins, minerals, and peptides are some of the 400 physiologically active substances. Anti-inflammatory, anti-ulcer, anti-diabetic, antiandrogenic, anti-aging, anti-fibrotic, antioxidant, hepatoprotective, sleep-promoting, anticarcinogenic, chemo and radioprotective, immunomodulation, estrogenic, and antibacterial properties are just a few of the numerous reported pharmacological effects. This review will help us to examine the role that this macro fungus holds in various therapeutic applications and how it can be a significant influence in the field of medicine.
Keywords: polysaccharides